2008
DOI: 10.1172/jci35834
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of CD4+Foxp3+ T cell accumulation during a human cutaneous antigen-specific memory response in vivo

Abstract: Naturally occurring CD4 + CD25 hi Foxp3 + Tregs (nTregs) are highly proliferative in blood. However, the kinetics of their accumulation and proliferation during a localized antigen-specific T cell response is currently unknown. To explore this, we used a human experimental system whereby tuberculin purified protein derivative (PPD) was injected into the skin and the local T cell response analyzed over time. The numbers of both CD4 + Foxp3 -(memory) and CD4 + Foxp3 + (putative nTreg) T cells increased in parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
117
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 65 publications
15
117
1
Order By: Relevance
“…They certainly differ from classical Tr1 because they express high levels of CD25, are Foxp3 + , and exert their suppressive function by direct cell-to-cell contact. In addition, recent data in a human setting seem to stress the functional and numerical relevance of adaptive Treg cells, which are likely constantly produced in the periphery from a differentiation stage that is equipped with suppressor functions (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They certainly differ from classical Tr1 because they express high levels of CD25, are Foxp3 + , and exert their suppressive function by direct cell-to-cell contact. In addition, recent data in a human setting seem to stress the functional and numerical relevance of adaptive Treg cells, which are likely constantly produced in the periphery from a differentiation stage that is equipped with suppressor functions (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent experimental evidence demonstrated that in humans, adaptive Treg cells may also emerge from the memory CD4 + CD25 2 CD45RO + T cell pool in the presence of antigenic stimulation. These converted Treg cells, once generated, are highly susceptible to apoptotic death, thus representing a highly dynamic T cell pool that mirrors its responsive counterpart (3)(4)(5).…”
mentioning
confidence: 99%
“…In humans, blood is readily accessible, and techniques such as skin biopsy and skin blister formation have been developed to sample the skin repertoire (18). However, although LN sampling is routine in animals, to date, techniques have not been developed to do so in humans.…”
mentioning
confidence: 99%
“…However, a growing body of evidence suggests that Tregs must enter tissues to be effective in regulation of local inflammation (21)(22)(23). The observation that healthy skin contains a resident population of Foxp3 + Tregs supports the concept that the ongoing presence of Tregs in organs, particularly those exposed to the external environment, is important in preventing inappropriate inflammation (24,25). Despite this, we know little about the mechanisms whereby Tregs recruited to peripheral tissues regulate local inflammation.…”
mentioning
confidence: 99%